Maladaptive repetition and career construction - Cardoso, Paulo (2013)
The role of repeated maladaptive relationship patterns established early in life has been widely studied with the goal of understanding the various factors and processes that contribute to and occur during development and psychological adaptation. The effects of maladaptive patterns have also been studied with regard to the goal of guiding interventions. The present article is intended to highlight the contribution of Career Construction Theory (CCT) for the integration of the concept of maladaptive repetition into the theory and practice of career counseling. It begins with a constructivist conceptualization of maladaptive repetition and proceeds to situate this concept within the contexts of both CCT and the constructivist conception of career indecision. The article then presents a case study, discusses difficulties that arise during career decision-making, and analyzes the maladaptive cycle rupture considering the client's perspective about her transformation.